A study on modeling of a piezoelectric motor - Youssef Baba; Mostafa Bouzi (Institute of Advanced Engineering and Science, 2021)
n this paper, a study on modeling of a piezoelectric transducer type rotary traveling wave ultrasonic motor (USM) is presented. First a mathematical model and numerical simulation results are achieved. The model is based on the theory of piezoelectricity and physic theory. An experimental model is worked out and compared to the numerical model. The influence of the temperature on characteristics such as the rotational speed of the motor is considered. The speed of the USM is measured at temperature between 17°Cand 50°C. To develop suitable control strategies for the drive, a fuzzy model type Takagi-Sugeno is used. The unknown parameters of the output membership functions are determined by least square method. Experimental data are used to examine the validity of the fuzzy model. Comparison between experimental and calculated data of the fuzzy model indicates that the fuzzy model can well describe the nonlinear characteristics among the frequency of driving voltage and rotating speed.